The Types and Structures of Lexical Bundles in Each Section of the Communications and Linguistics Academic Articles - Fidela Artha, Almira (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
Considering the importance of Lexical Bundles (LBs) in Applied English Linguistics, several studies had been conducted in the recent years. The previous studies mainly compared the LBs between genres and between native speakers and non-native speakers. There has yet to be any study that combines the LBs from each section of the same academic writing and the LBs of two related disciplines. This study focuses on the types and structures of LBs in each section of academic articles published in an international journal. This study also compares the LBs found in two related disciplines, i.e., Communications and Linguistics. This study found that the variation of LBs is not only different by disciplines but also by the sections. The co-occurrence      of LBs in Communication Introduction and Method is less compared to Linguistics. LBs in Communication suggest a more straightforward and clear method of conveying information.      Linguistics, meanwhile, shows complexity competence and greater engagement with abstract concepts and specialized vocabulary. The trends of dominant LB structure in every section are preposition and noun-based LBs, which have higher writing quality and complexity. The findings of this study are expected to highlight the importance of LBs in academic writing.